2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944252
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive workload estimation due to vague visual stimuli using saccadic eye movements

Abstract: Visual perception is affected by the quality of stimulus. In this paper, we investigate the rise in cognitive workload of an individual performing visual task due to vague visual stimuli. We make use of normalized average peak saccadic velocity to estimate the cognitive workload. Results obtained from 16 human subjects show that the mean of peak saccadic velocity increases with workload indicating that faster saccades are required to obtain information as the workload increases. This technique should find appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Specifically, peak saccade velocity as a measure is sensitive enough to distinguish among all levels of mental attentional demand with the exception of the highest two levels, which were generally either at or above the limit of participant's mental attentional capacity. The direction of the relation between mental attentional demand and eye movements is consistent with some past studies ( Di Stasi et al., 2010 ; Savage et al., 2020 ) but not others ( Bodala et al., 2014 ). Specifically, Di Stasi et al.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, peak saccade velocity as a measure is sensitive enough to distinguish among all levels of mental attentional demand with the exception of the highest two levels, which were generally either at or above the limit of participant's mental attentional capacity. The direction of the relation between mental attentional demand and eye movements is consistent with some past studies ( Di Stasi et al., 2010 ; Savage et al., 2020 ) but not others ( Bodala et al., 2014 ). Specifically, Di Stasi et al.…”
Section: Discussionsupporting
confidence: 91%
“…The average peak saccadic velocity is found to have a positive relationship with the increasing workload [156] and more specifically, it has been shown to be more sensitive to germane load [148]. The significance of saccadic velocity in determining the amount of cognitive load is demonstrated also through video game scenarios.…”
Section: Metrics Related To Cognitive Workloadmentioning
confidence: 85%
“…Rosch and Vogel-Walcutt’s (2013) review also showed that increased average fixation durations correspond with increases in cognitive load. Moreover, Bodala, Ke, Mir, Thakor, and Al-Nashash (2014) used peak saccade velocity as a measure of cognitive load and concluded that higher cognitive load requires faster saccades. To sum up, a variety of measures have been proposed to quantify cognitive load, but it remains an open question up to the present which of these measures is most reliable.…”
Section: Toward An Integrative Taxonomy Of Eye-tracking Researchmentioning
confidence: 99%